Genie: new software for rapid submission of powder diffraction data to the ICDD powder diffraction file™. Issue 2 (10th November 2014) - Sagnella, Diane E.; Foster, Emily
<x content-type="archive" xml:space="preserve">Abstract</x> A new software application has been developed to provide a convenient method for the submission of diffraction data directly to the International Centre for Diffraction Data, for inclusion in the Powder Diffraction File (PDF)™. The application, titled Genie, acts as a portal for the merging of data from separate sources allowing the user to quickly and easily submit their data for the PDF. Using Java Web Start technology Genie can be run using all common computer platforms. Genie is flexible and can be used to read a variety of common file formats. Furthermore, Genie can also be used for submission of New Diffraction Data for publication in the Powder Diffraction Journal.